Design of semisynthetic derivatives of the Amaryllidaceae alkaloid ambelline and exploration of their in vitro cytotoxic activities - Ritomská, Aneta; Koutova, Darja; Křoustková, Jana; Královec, Karel; Muthná, Darina; Kuneš, Jiří; Nováková, Lucie; Havelek, Radim; Cahlíková, Lucie (Saudi pharmaceutical journal, 2023)
Ambelline, an alkaloid from the Amaryllidaceae family with a crinane-type skeleton, has not yet demonstrated any outstanding biological activity. However, its analogues prepared by derivatization of the C-11 hydroxyl group show different interesting effects. Continuing our earlier work, twelve novel aromatic esters were developed (10, 14, 16, 17, 22-25, 30-33) and studied, together with previously synthesized derivatives (2-9, 11-13, 15, 18-21, 26-29) in terms of their cytotoxic activity. The cytotoxic potential was determined on a panel of nine human cancer cell lines and one noncancerous cell line to characterize their biological activity spectrum. To describe and foresee the structure-activity relationship for further research, substances synthesized and described in our previous work were also included in this cytotoxicity study. The most significant activity was associated with analogues having methyl (10), methoxy (14-17), or ethoxy (18) substitution on the phenyl condensed to ambelline. However, the 4-chloro-3-nitrobenzoyl derivative (32) showed the most promising IC50 values, ranging from 0.6 ± 0.1 µM to 9.9 ± 0.2 µM. In vitro cytotoxicity studies indicated the most potent antiproliferative activity of 32 in a dose-dependent and time-dependent manner. Besides, 32 was found to be effective in decreasing viability and triggering apoptosis of MOLT-4 T-lymphoblastic leukemia cells.
Keywords: Amaryllidaceae alkaloids; 11-O-(4-Chloro-3-nitrobenzoyl)ambelline; Ambelline; In vitro; Cytotoxicity; Antiproliferative activity